Cross-Industry Differentiation High Technology Sector in The European Union - Magdalena ŁADA (Communications of International Proceedings, 2022)
The high-tech sector plays an important role in shaping the global economy. It is a combination of the advanced technology industry and knowledge-intensive technologically advanced services. Due to the diversity of the companies that operate in it, the research is aimed at preliminary determination of the inter-industry diversity of the high-tech sector in the European Union. This analysis made it possible to identify the industry that determines the innovative potential and competitiveness of the entire sector to the highest degree. The starting point for the considerations was to define and classify the high technology sector, then, on the basis of the available data in the Eurostat database, the share of expenditure on research and development (R&D) in GDP per capita of individual industries assigned to the high technology sector was analyzed. Possible directions of future research in this field were also indicated.
Keywords: high technology sector; technologically advanced manufacturing industries; high-tech services industries; R&D